(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
There is no secret that a reliable financial information and an effective accounting system play a great role in the economies. Reliable financial reporting ensures greater economic growth, better allocation of resources, lower capital costs, wider comparability for investors and more willingness of those to invest across borders. From this perspective, it is understood the wide spread of International Accounting Standards around the world, which are simply presented as uniform standards applicable in different countries with the aim of achieving an international accounting consensus in which the comparability of financial statements is enhanced, thus enhancing the universality of capital markets. On the other hand, there is controversy about the benefits of International Accounting Standards for developing countries, starting from the difficulty of applying a common standard to a group of countries with varying circumstances, arriving to problems of implementation, some of which are due to the environment of developing countries themselves, while others are due to international standards requirements themselves. According to their position on the application of the standard, developing countries are divided between countries that have imposed mandatory adoption of standards (partial or total) and others that allowed adoption and others that have not. Syria is one of the countries that opted for partial mandatory adoption of standards in the context of its economic openness and integration into the world economy in the first 10 years of the third millennium. This research aims to evaluate the adoption of the International Accounting Standards in the Syrian environment, which was mandated by Decree 55 in 2006 and which obliges all entities subject to the supervision of the Syrian Securities and Financial Markets Authority to prepare its financial statements and reports according to the mentioned standards. Despite the short period of adoption for developing countries in general and for Syria in particular due to the outbreak of the 2011 crisis, our assessment will focus on verifying compliance with adoption requirements, identifying implementation problems, and whether there are more successful approaches to adopting standards that fit With the conditions of the country. Case studies from many developing countries that had already adopted standards and known difficulties and problems will be used. It will be important to identify their experiences in order to learn from them to avoid failures and devote success points, taking into account the specificity of the current phase for the Syrian case. The study concludes that in the Syrian case it is necessary to review the accounting situation of the country and the ability of its accounting institutions to the international accounting standards in the context of the Syrian crisis and to know if there is a need to pass laws or legislation to facilitate the process of transition to those standards and to mitigate the conflict with them and to correct the mistakes that occurred during the adoption process.